Differential associations of positive and negative expectations with depressive symptoms. Issue 3 (14th September 2022) - Kube, Tobias; Herzog, Philipp
Abstract: Background: Recent research suggests that dysfunctional expectations are a particularly important subtype of cognitions in depression. However, it is unclear whether depressive symptoms are related to the presence of negative expectations, the absence of positive expectations, or both. Methods: Using hierarchical linear regression analyses, the present study examined the predictive value of positive situation‐specific expectations, negative situation‐specific expectations, dispositional optimism, and dysfunctional attitudes for depressive symptoms 8 weeks later in a nonclinical sample ( N = 157). It also examined whether the relationship between dispositional optimism and dysfunctional attitudes with depressive symptoms is mediated through situational expectations. Results: Cross‐sectionally, depressive symptoms were more strongly associated with the presence of negative expectations than with the absence of positive expectations. In the longitudinal and mediation analyses, none of the cognitive variables had significant associations with depressive symptoms at follow‐up beyond the strong influence of baseline depressive symptoms. Conclusions: The presence of negative expectations was cross‐sectionally more strongly associated with depressive symptoms than a lack of positive expectations, presumably due to higher variability in negative expectations in this nonclinical sample. The longitudinal and mediation analyses failed to find significant incremental effects of any of the cognitive variables because baseline depression explained the largest proportion of variance.